UK 2022 Consensus on Normal Tissue Dose-Volume Constraints for Oligometastatic, Primary Lung and Hepatocellular Carcinoma Stereotactic Ablative Radiotherapy. Issue 5 (May 2022) - Diez, P.; Hanna, G.G.; Aitken, K.L.; van As, N.; Carver, A.; Colaco, R.J.; Conibear, J.; Dunne, E.M.; Eaton, D.J.; Franks, K.N.; Good, J.S.; Harrow, S.; et al.
Abstract: The use of stereotactic ablative radiotherapy (SABR) in the UK has expanded over the past decade, in part as the result of several UK clinical trials and a recent NHS England Commissioning through Evaluation programme. A UK SABR Consortium consensus for normal tissue constraints for SABR was published in 2017, based on the existing literature at the time. The published literature regarding SABR has increased in volume over the past 5 years and multiple UK centres are currently working to develop new SABR services. A review and update of the previous consensus is therefore appropriate and timely. It is hoped that this document will provide a useful resource to facilitate safe and consistent SABR practice.